Formaldehyde-induced damage in lungs and effects of caffeic acid phenethyl ester: A light microscopic study - Türko?lu, Asli Özdem; Sarsilmaz, Mustafa; Çolako?lu, Neriman; Zararsiz, Ismail; Kulo?lu, Tuncay; Pekmez, Hidir; Taş, Ufuk (My University, 2008)
Aim: The aim of this study was to investigate the toxicity of formaldehyde on lung and protective effects of caffeic acid phenethyl ester against these toxic effects. Methods: For this purpose, 21 male Wistar rats were divided into three groups. The rats in Group I comprised the controls, while the rats in Group II were injected with formaldehyde (FA). The rats in Group III received CAPE daily while exposed to formaldehyde. After the treatment, lungs tissues were evaluated by microscopic examination. Results: In the microscopic examination of FA group, fatty and cellular infiltration in the pulmonary interstitium and thickening in the bronchiolar wall were evident. Dilatation and congestion were prominent in the alveolar septal vessels. In FA+CAPE group, dilatation of interalveolar septal vessels was less observed than FA group. Bronchial wall structures are similar with control. Conclusion: It was thought that FA exposure leads to inflammation and injury in lungs. CAPE shows protective and anti inflammatory activity against these adverse effects.
Keywords: Caffeic acid phenethyl ester; Formaldehyde; Lung